ANALISIS KETAHANAN PANGAN RUMAH TANGGA PETANI UBI KAYU DI KABUPATEN LOMBOK TENGAH - Hidayanti, Anna Apriana; Mandalika, Eka Nurminda Dewi (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2025)
Food security at the farmer household level can be measured through several indicators, one of which is income and food and non-food expenditure. These factors can be a reference to see household-level food security. The greater the income, the greater the purchasing power and thus the greater the level of household welfare. One of the many agricultural products in Indonesia is cassava. In an effort to maintain the stability of food security of cassava farmers, this study aims to determine what factors affect the food security of cassava farming households in Central Lombok Regency. With the dependent variable is market share and the independent variable is the level of monthly income, participation in PKK activities, the number of dependents and age and food and non-food expenditures. And the results of this study are variables that have a significant influence on the food security of farmer households are participation in PKK activities and household expenditures of cassava farmers, with a significant value of 0.03 less than the value of 0.05, and the second variable that has a significant influence on household food security is the variable food and non-food expenditure of 0.0001.